Seroprevalence of seven pathogens transmitted by the Ixodes ricinus tick in forestry workers in France. (August 2016) - Rigaud, E.; Jaulhac, B.; Garcia-Bonnet, N.; Hunfeld, K.-P.; Féménia, F.; Huet, D.; Goulvestre, C.; Vaillant, V.; Deffontaines, G.; Abadia-Benoist, G.
Abstract: In order to assess the level of occupational exposure to the main pathogens transmitted by the Ixodes ricinus tick, a seroprevalence study was performed on serum samples collected in 2003 from 2975 forestry workers of northeastern France. The global seroprevalence estimated for the seven pathogens studied was 14.1% (419/2975) for Borrelia burgdorferi sl, 5.7% (164/2908) for Francisella tularensis, 2.3% (68/2941) for tick-borne encephalitis virus, 1.7% (50/2908) for Anaplasma phagocytophilum and 1.7% (48/2908) for Bartonella henselae . The seroprevalences of Babesia divergens and Babesia microti studied in a subgroup of participants seropositive for at least one of these latter pathogens were 0.1% (1/810) and 2.5% (20/810), respectively. Borrelia burgdorferi sl seroprevalence was significantly higher in Alsace and Lorraine and F. tularensis seroprevalence was significantly higher in Champagne-Ardenne and Franche-Comté. The results of this survey also suggest low rates of transmission of Bartonella henselae and F. tularensis by ticks and a different west/east distribution of Babesia species in France. The frequency and potential severity of these diseases justify continued promotion of methods of prevention of I. ricinus bites.